Cycle checking algorithm for verifying the connectivity of a fault tolerant network structure - B, Nethravathi; V. N, Kamalesh (International Journal of Engineering and Technology, 2018)
The key challenges while designing a communication network structures and critical network topologies is to take accounts of aspects related to failures. Over years efforts are being made for constructing quality fault tolerance network structures. The performance of a network application depends on the stability and survivability of underlined interconnection network structure. Node â€“connectivity of a network graph is a globally accepted deterministic measure for measuring the fault tolerance in a network structure. Once the network is designed and constructed by any one of the existing design algorithm and claimed that the constructed network is k-connected network, this research paper proposes a cute cycle based method to verify the same.Â